2017
DOI: 10.1155/2017/5872068
|View full text |Cite
|
Sign up to set email alerts
|

The Outcome of Thoracentesis versus Chest Tube Placement for Hepatic Hydrothorax in Patients with Cirrhosis: A Nationwide Analysis of the National Inpatient Sample

Abstract: There are only a few studies with a small sample size of patients that have compared the risks of using chest tubes versus thoracentesis in hepatic hydrothorax. It has been shown that many complications may arise secondary to chest tube placement and is associated with increased morbidity and mortality. In this retrospective study, patients with cirrhosis were identified from the 2009 National Inpatient Sample by using ICD-9 codes; we evaluated the risk of chest tube versus thoracentesis in a largest populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This has been demonstrated in studies of cirrhotic patients who experience greater mortality and longer length of stay with chest tube drainage than with thoracentesis. 30,31 It would also be valuable to compare pleural fluid drainage procedures with aggressive diuresis in patients who have a positive fluid balance and whose pleural effusions are most likely secondary to volume overload. 2,9 In addition, future studies should evaluate pleural fluid drainage for its various purposes: improved diagnostics, improved pulmonary mechanics or oxygenation, or stopping clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…This has been demonstrated in studies of cirrhotic patients who experience greater mortality and longer length of stay with chest tube drainage than with thoracentesis. 30,31 It would also be valuable to compare pleural fluid drainage procedures with aggressive diuresis in patients who have a positive fluid balance and whose pleural effusions are most likely secondary to volume overload. 2,9 In addition, future studies should evaluate pleural fluid drainage for its various purposes: improved diagnostics, improved pulmonary mechanics or oxygenation, or stopping clinical deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…( 70 ) In a recent retrospective study of 140,573 patients with liver cirrhosis, among whom 1,981 had HH requiring thoracentesis (1,776) or chest tube (205), hospital length of stay and mortality rate for chest tube patients were double those for thoracentesis patients. ( 71 ) For these reasons, the American Association for the Study of Liver Diseases guidelines state that “Chest tube insertion is contraindicated in patients with hepatic hydrothorax.” ( 32 ) Chest tube, however, may be indicated in the management of infected pleural fluid (Table 1), preferably with a smaller‐bore (<20 F) drain. The details of chest tube placement and management are beyond the scope of this review but could be of interest to the reader when infected pleural fluid is encountered.…”
Section: Multidisciplinary Management Of Hhmentioning
confidence: 99%
“…High volume drainage of fluid and re-accumulation of pleural fluid on clamping intercostal drains is characteristic. As a result, repeat thoracentesis has been the routine procedure for removal of pleural fluid from the pleural cavity and has been shown to have reduced mortality and hospital stay compared to chest drain insertion ( 16 ). However, a single centre retrospective review of patients undergoing thoracentesis showed the cumulative risk of complications increased with sequential thoracenteses ( 17 ), with increased risk of haemothorax with thrombocytopenia and higher MELD scores (Model for End-Stage Liver Disease which stratifies severity of liver disease).…”
Section: Discussionmentioning
confidence: 99%